2022
DOI: 10.4102/ajod.v11i0.807
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the awareness and knowledge of dyslexia among primary school teachers in Tshwane District, South Africa

Abstract: Background: Many developed countries have made rapid strides in addressing issues related to dyslexia but in the developing countries like South Africa, it has not received adequate attention.Objectives: The study therefore sought to evaluate awareness and knowledge of dyslexia among primary school teachers working in the government sector.Methods: A phenomenological design was used and the study followed a mixed methods approach. The sample included 30 purposively selected primary school teachers. A questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…A study carried out by Makgato et al (2022) to determine the awareness and understanding of dyslexia among primary school tutors in Tswane County, South Africa, indicated that these tutors have minimal awareness and understanding of dyslexia. In developed nations, tremendous progress has been made in addressing matters associated with dyslexia, unlike in low-and middle-income nations like South Africa, where it has not received appropriate attention.…”
Section: Research Studies Done On Dyslexiamentioning
confidence: 99%
“…A study carried out by Makgato et al (2022) to determine the awareness and understanding of dyslexia among primary school tutors in Tswane County, South Africa, indicated that these tutors have minimal awareness and understanding of dyslexia. In developed nations, tremendous progress has been made in addressing matters associated with dyslexia, unlike in low-and middle-income nations like South Africa, where it has not received appropriate attention.…”
Section: Research Studies Done On Dyslexiamentioning
confidence: 99%
“…Afrikaans and Sepedi) are transparent. However, irrespective of the common occurrence and nature of dyslexia, both internationally and on African soil, the disorder and its accompanying challenges of low resources and socio-economic factors have not received adequate attention in most developing countries (Makgatho et al 2022). Schools require support not only in using resource models but also in providing adequate emotional support to their learners (Rao et al 2017:163).…”
Section: International Perspectives Of Dyslexia Managementmentioning
confidence: 99%
“…It argues that dyslexia is not a disorder but a specific learning disorder. Many authors come to a consensus that dyslexia are linked 1 Unit of Phoniatrics, Otorhinolaryngology Department, Banha teaching Hospital, Al Qalyubia and 2 Unit of Phoniatrics , Otorhinolaryngology Department, Faculty of Medicine, Ain Shams University, Cairo.…”
Section: Introductionmentioning
confidence: 99%